2018
DOI: 10.1371/journal.pntd.0006575
|View full text |Cite
|
Sign up to set email alerts
|

Genetic manipulation of Leishmania donovani threonyl tRNA synthetase facilitates its exploration as a potential therapeutic target

Abstract: BackgroundAminoacyl tRNA synthetases are central enzymes required for protein synthesis. These enzymes are the known drug targets in bacteria and fungi. Here, we for the first time report the functional characterization of threonyl tRNA synthetase (LdThrRS) of Leishmania donovani, a protozoan parasite, the primary causative agent of visceral leishmaniasis.MethodologyRecombinant LdThrRS (rLdThrRS) was expressed in E. coli and purified. The kinetic parameters for rLdThrRS were determined. The subcellular localiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 38 publications
(53 reference statements)
0
10
0
Order By: Relevance
“…The borrelidins have attracted significant attention from the natural products community, and their noteworthy anti‐infective and cytotoxic activities have especially drawn the interest and efforts of biosynthetic and chemical synthesis researchers . In this study, three new borrelidins ( 1 – 3 ), along with four previously reported family members ( 4 – 7 ), were isolated from a likely associated symbiont S. olivaceus SCSIO LO13 from the marine pulmonated mollusk Onchidium sp.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The borrelidins have attracted significant attention from the natural products community, and their noteworthy anti‐infective and cytotoxic activities have especially drawn the interest and efforts of biosynthetic and chemical synthesis researchers . In this study, three new borrelidins ( 1 – 3 ), along with four previously reported family members ( 4 – 7 ), were isolated from a likely associated symbiont S. olivaceus SCSIO LO13 from the marine pulmonated mollusk Onchidium sp.…”
Section: Discussionmentioning
confidence: 88%
“…Borrelidin A ( 4 ) was the first member of the family discovered and has been shown to have antibiotic and antimalarial activities as well as the ability to inhibit tumorigenic and angiogenic processes . Borrelidin A ( 4 ) has been particularly important in demonstrating the importance of threonyl tRNA synthetase (ThrRS) inhibition as a viable means of targeting the causative agent for malaria . Although borrelidin A ( 4 ) is toxic to non‐malignant cell types, its antitumor potential, as reflected in part by its ability to inhibit the growth of hepatocellular carcinoma cells, has garnered a significant amount of clinical interest .…”
Section: Introductionmentioning
confidence: 99%
“…The gene coding for a threonyl-tRNA synthetase was overexpressed in acidic condition ( S6B Table ). This enzyme family, involved in the protein translation machinery, is often used as a target in a wide range of antibiotics [ 30 ], and its inactivation led to a reduced growth and attenuated virulence in Leishmania donovani [ 31 ]. In the same way, the regulation of its expression in G .…”
Section: Resultsmentioning
confidence: 99%
“…Experimental studies on NSP15 have revealed that His-235, His-250, and Lys-290 (Ricagno et al 2006) are the critical residues for catalysis that are located in the C-terminal domain of the enzyme. Docking studies were performed using GOLD (Jones et al 1997), and the protein was kept as a rigid molecule, and the number of Genetic Algorithm (GA) runs was set to 10 runs per ligand with the default search algorithm parameters similar to our earlier reports (Vijayan and Mallick 2007;Eniyan et al 2018;Chadha et al 2018; Vijayan and Manohayan 2015; Mahendran and Vijayan 2018). GOLD score was then used as the final scoring method.…”
Section: Docking-based Virtual Screeningmentioning
confidence: 99%